Compliance Management and Islamic Bank Reputation: Service Quality Mediation in Gresik - Muhammad Yusuf Aria Widjaja; M. Ridlwan Hasyim; Fellasufah Diniyah; Duta Bintan Fitriyah (Universitas Negeri Padang, 2026)
Islamic banks are expected to translate Sharia compliance into service experiences that shape public trust. Yet, few studies treat corporate reputation as the joint outcome of compliance management and service quality. This study tests a model linking compliance management, service quality, and corporate reputation among community members in six northern subdistricts of Gresik Regency, Indonesia. Cross-sectional data from 96 respondents, selected through purposive sampling, were analyzed using PLS-SEM in SmartPLS 4, with the path-weighting scheme and 5,000 bootstrap subsamples. The measurement model showed convergent validity and reliability (outer loadings > 0.70; AVE = 0.737–0.785; composite reliability > 0.89), though discriminant validity was not established (HTMT = 0.984–0.993). Compliance management predicted service quality (β = 0.922, p < .001) and corporate reputation (β = 0.275, p = .003), while service quality predicted corporate reputation (β = 0.693, p < .001). Service quality partially mediated the compliance–reputation relationship (complementary pattern; indirect effect β = 0.639, p < .001; VAF = 69.91%), and the model explained substantial variance in service quality (R² = 0.850) and corporate reputation (R² = 0.908). Compliance thus strengthens reputation directly, as a signal of institutional integrity, and indirectly, through service experiences that make compliance tangible. Given elevated collinearity and common-method diagnostics, these results are preliminary and warrant replication with more discriminant measures and multi-source data. The study contributes by positioning service quality as the mechanism converting internal compliance into external reputational capital, with implications for aligning compliance, product, and frontline service functions in community-based Islamic banks.